Miscibility, Thermal, Morphological and Mechanical Behaviour of Polycarbonate/poly(trimethylene terephthalate)blends with Poly(butylene adipate-co-terephthalate) as a Compatibilizer - Kim, S.B.; Kim, H.R.; Nam, B.U. (Asian Journal of Chemistry, 2013)
The thermal, mechanical and morphological behaviour of polycarbonate (PC), poly(trimethylene terephthalate) (PTT) and poly(butylene adipate-co-terephthalate) (PBAT) polymer blends were investigated. Several blends were prepared by a melt mixing process using a twin-screw extruder. Dynamic mechanical analysis and field emission scanning electron microscopy showed that PC/PTT binary blends provide a compatible system. In the PC/PTT/PBAT ternary blends, poly(butylene adipate-co-terephthalate) led to improved compatibility. In particular, the PC20PTT80BA composition was a miscible system. The thermal degradation and mechanical properties were characterized by thermogravimetric analysis and a notched-izod impact test, respectively. The results showed that that poly(butylene adipate-co-terephthalate) plays an important role as a compatibilizer in PC/PTT/PBAT blends.